2017
DOI: 10.1111/ases.12365
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic transabdominal preperitoneal approach for umbilical hernia with rectus diastasis

Abstract: The laparoscopic transabdominal preperitoneal approach for umbilical hernia and rectus diastasis may be a safe surgical option when trying to avoid potential complications related to intra-abdominal mesh positioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Although this preperitoneal space may be rather delicate above the arcuate line and may contain insufficient connecting tissue, it can usually still be carefully and meticulously separated, establishing a sufficient extraperitoneal (preperitoneal) pocket to accommodate a large non-coated mesh for hernia repair. Several surgeons have tried to use this extraperitoneal plane for optimal mesh placement and such to avoid any violation of the rectus sheath or the linea alba [15][16][17]. However, in all of these studies, the transabdominal route for approaching this extraperitoneal space was used.…”
Section: Discussionmentioning
confidence: 99%
“…Although this preperitoneal space may be rather delicate above the arcuate line and may contain insufficient connecting tissue, it can usually still be carefully and meticulously separated, establishing a sufficient extraperitoneal (preperitoneal) pocket to accommodate a large non-coated mesh for hernia repair. Several surgeons have tried to use this extraperitoneal plane for optimal mesh placement and such to avoid any violation of the rectus sheath or the linea alba [15][16][17]. However, in all of these studies, the transabdominal route for approaching this extraperitoneal space was used.…”
Section: Discussionmentioning
confidence: 99%
“…However, transfascial sutures are painful beyond the higher cost associated with intraperitoneal meshes. The closure of the defect with placement of large preperitoneal meshes to reinforce peri-hernia weakness - known as umbilical TAPP - in patients who do not need or wish to correct diastasis has recently been used 7 , 16 .…”
Section: Discussionmentioning
confidence: 99%
“…It is optional to simultaneously correct the diastasis; this should be discussed with the patient [28]. When seeking to prevent potential issues linked to intra-abdominal mesh positioning, the laparoscopic TAPP technique for umbilical hernia and rectus diastasis may be a safe surgical choice [29]. Shinde et al [27] examined the SCOLA with an added modification of the operating port, using spinal needles to restrict the amount of lateral dissection, and found that with little risks and postoperative morbidities, SCOLA is an effective surgery for treating umbilical/epigastric hernia with diastasis recti [27].…”
Section: Preferred Mas Procedures For Umbilical Hernia With Diastasis...mentioning
confidence: 99%